Pengaruh BOPO, CAR, Pembiayaan Mudharabah dan Pembiayaan Murabahah terhadap Return On Asset (ROA) Bank Umum Syariah Indonesia Periode 2020-2022 - Iswara, Gyusti Febrian; Adlan, Muhammad Aqim (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2024)
he purpose of this research is to look at the impact of Operating Costs on Operating Income (BOPO), Mudharabah Financing, Capital Adequacy Ratio (CAR), and Murabahah Financing on the Return on Assets (ROA) of Islamic commercial banks in Indonesia from 2020 to 2022. The study's sample consists of Islamic commercial banks whose financial reports are included in Islamic banking statistics. Purposeful sampling technique was used to choose the sample. Utilizing Eviews 12 software, multiple linear regression analysis is the data analysis approach employed in this quantitative research method. The findings demonstrate that CAR, Mudharabah Financing, and Murabahah Financing have a substantial impact on the ROA of Islamic commercial banks in Indonesia, however BOPO has no effect on the dependent variable. This study contributes significantly to our understanding of the elements that determine the ROA of Islamic commercial banks in Indonesia. The findings of the study can help bank management make more effective decisions to improve financial performance. Further research could include more variables or prolong the study period to obtain a more complete picture of the factors influencing the ROA of Islamic commercial banks in Indonesia. Keywords: BOPO, CAR, Mudharabah Financing, Murabahah Financing, and ROA